Communication strategies to enhance professionalism [videorecording (DVD)] - Geithner, Christina A. (Healthy Learning video lecture series, 2006)
This video is aimed at developing better communication skills, with a look at specific communication-related strategies that individuals can employ to enhance their level of professionalism. What it means to be a professional and the role of communication in professionalism are addressed. Consideration is given to pre-presentation or meeting activities, the actual presentation or meeting, and post-presentation or follow-up activities. Practical suggestions concerning how to effectively deal with the various types of communication-related circumstances are provided in order to enhance the ability of professionals to be successful in a particular setting, regardless of their discipline or occupational field. Among the topics covered in the video: The communication process, elements of communication, common barriers to communication, tips for successful communication, and strategies to enhance professionalism.